DiaPASEF proteotype analysis indicates changes in cell growth and metabolic switch induced by caspase-9 inhibition in chondrogenic cells - Lapcik, Petr; Vesela, Barbora; Potesil, David; Dadakova, Katerina; Zapletalova, Martina; Benes, Petr; Bouchal, Pavel; Matalova, Eva (Proteomics, 2023)
Caspase-9 is the major apical caspase responsible for triggering the intrinsic apoptotic pathway. Our previous study indicated that specific inhibition of caspase-9 caused microscopically evident alterations in appearance of the primary chondrogenic cultures which cannot be explained by decrease in apoptosis. To describe a complex molecular background of this effect, proteomics analysis of control and caspase-9 inhibitor-treated chondrogenic cultures were performed. Proteins were extracted, identified and quantified using LC-MS in both data dependent and data independent acquisition (DIA) mode. While directDIA analysis of diaPASEF data obtained using timsTOF Pro LC-MS system revealed 7849 protein groups (Q-value <0.01), a parallel analysis of iTRAQ-2DLC-MS3 and conventional DIA-MS data identified only 5146 and 4098 protein groups, respectively, showing diaPASEF a superior method for the study. The detailed analysis of diaPASEF data disclosed 236/551 significantly down-/up-regulated protein groups after caspase-9 inhibition, respectively (|log2FC|>0.58, Q value <0.05). Classification of downregulated proteins revealed changes in extracellular matrix organization, collagen metabolism, and muscle system processes. Moreover, deregulations suggest a switch from glycolytic to lipid based metabolism in the inhibited cells. No essential changes were found in the proteins involved in apoptosis. The data indicate new non-apoptotic participation of caspases in chondrocyte homeostasis with potential applications in cartilage pathophysiology.
Keywords: apoptóza; signální transdukce; Signal Transduction; Caspase 9; kaspasa 9; Chondrocytes; Caspases; kaspasy; Apoptosis; chondrocyty